Case of a woman with acromegaly whose presenting complaint was prolonged post‐partum amenorrhea. Issue 10 (19th July 2016) - Hara, Tomomi; Kanasaki, Haruhiko; Oride, Aki; Moriyama, Masayuki; Kyo, Satoru
Abstract: We report a case of a woman who was incidentally diagnosed with acromegaly after referral for prolonged post‐partum amenorrhea. A 25‐year‐old woman, gravida 2 para 1, had a normal transvaginal delivery and breastfeeding had been discontinued more than a year after delivery. Thereafter, spontaneous menstruation did not restart and she underwent hormonal therapy. Subsequently, she was referred to our university hospital for prolonged amenorrhea. Hormonal examination revealed severe hypogonadotropic hypogonadism (luteinizing hormone 0.5 mIU/mL, follicle‐stimulating hormone < 1.0 mIU/mL, estradiol 13 pg/mL), along with a modest increase in serum prolactin levels (43.2 ng/mL). She also complained of milk ejection on nipple stimulation. Magnetic resonance imaging of the head was performed, because an organic abnormality in the central nervous system was suspected to be causing the amenorrhea, which revealed mass lesions extending from the pituitary fossa to the suprasellar area with similar signal intensity as the gray matter. In addition, bitemporal hemianopsia was observed on campimetry. After further examination, the patient was diagnosed with acromegaly.